Precise Positional Adjustments with Laser-Induced Shock Waves - Bechtold, Peter; Roth, Stephan; Schmidt, Michael (Photonics Spectra, 2008)
A micro- and nanoscale adjustment process to achieve precise positioning within defined tolerances has been developed at the Bayerisches Laserzentrum. The adjustment process uses ultrashort laser pulses to induce a microshock wave in the workpiece, resulting in a highly controllable, subnanometer deformation of the piece. This process can be used in different materials, and the interaction mechanism is almost nonthermal. This adjustment process has negligible thermal impact on the workpiece.
LFT Import::2019-07-29 (1520)